SURVEY OF Salmonella spp and E. coli IN DRINKING WATER OBTAINED FROM SOME SELECTED LOCAL GOVERNMENT AREAS IN ADAMAWA STATE, NIGERIA - M. KABIRU, AMINA; KABIRU, SANUSI M. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The aim of this research is to determine some bacteriological composition in drinking water (wells and bore-holes) at Mubi-north, Girei and Mayo-Belwa local government areas of Adamawa state, Nigeria. Various types of bacteria/viruses are categorized as pathogens, disease causing organisms that can be found in pretreated or inadequately treated water. Water, being dynamic, needs to be constantly analyzed to minimize contaminants that could be detrimental to the consumers. E. coli and fecal coliform are bacteria whose presence can indicate water contaminated by human or animal wastes, causing short-term health effects. When there is seepage of contaminant through well casing, cracks or holes in the well casing allow water that has not been filtered through the soil to enter the well. This seepage is common in the wells made of concrete, clay tile, or brick. These are the nature of wells commonly found across the study areas. Most of the bole holes are hand dug, shallow, located close to river banks where refuse and farming activities characterized by bush burning, application of fertilizers, animals and human defecation is the order day due to these reasons, water sources across the study areas are vulnerable to different kinds of contamination. Investigation into water quality is not a relatively new phenomenon but literature concerning the quality of drinking water from the study is sparse. 62 water Samples were collected at random from both well and boreholes at different location within the study areas using containers with earlier prepared nutrient broth. Three different media were prepared adhering strictly to the media manufacturer’s instruction. For the determination of E. coli, 24g of EMB was used and SS agar was used for Salmonella species. Results shows that in well water during rainy season the mean concentration of salmonella spp. ranged from (153– 272 CFU/ml), Total coliforms, well water during rainy season mean concentration ranged from (418 – 624 CFU/ml), During dry season, values ranged from (81 – 126 CFU/ml), while for E.coli, in well water during rainy season, the mean values ranged from (33 – 71 CFU/ml),. During dry season ranged from (97. – 131 CFU/ml), conclusively, findings indicates significant higher bacteriological composition in well water during rainy season than dry season (p<0.05). Hence, calls further research and monitoring.